Space in language and cognition : explorations in cognitive diversity - Levinson, Stephen C.; Max Planck Institut für Psycholinguistik (Nijmegen, Netherlands) (Cambridge ; New York : Cambridge University Press, 2003)
"Languages differ in how they describe space, and such differences between languages can be used to explore the relation between language and thought. This book shows that even in a core cognitive domain, such as spatial thinking, language influences how people think, memorize and reason about spatial relations and directions. After outlining a typology of spatial coordinate systems in language and cognition, it is shown that not all languages use all types, and that non-linguistic cognition mirrors the systems available in the local language. The book reports on collaborative, interdisciplinary research, involving anthropologists, linguists and psychologists, conducted in many languages and cultures around the world, which establishes this robust correlation. The overall results suggest that most current thinking in the cognitive sciences underestimates the transformative power of language on thinking. The book will appeal to all researchers interested in the relation of language to other areas of cognition - linguists, psychologists, anthropologists, philosophers - and especially to students of spacial cognition."--Jacket
1. The intellectual background: two millennia of Western ideas about spatial thinking -- 2. Frames of reference -- 3. Linguistic diversity -- 4. Absolute minds: glimpses into two cultures -- 5. Diversity in mind: methods and results from a cross-linguistic sample -- 6. Beyond language: frames of reference in wayfinding and pointing -- 7. Language and thought.
Includes bibliographical references (pages 348-367) and indexes.
Print version record.
eBooks on EBSCOhost
Keywords: Space and time in language; Psycholinguistics; Cognition; Psycholinguistics; Cognition; Espace et temps dans le langage; Psycholinguistique; Cognition; psycholinguistics; cognition; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Psycholinguistics; Cognition; Psycholinguistics; Space and time in language; Kognition; Psycholinguistik; Raumvorstellung; Sprache; Taal; Cognitie; Ruimte (algemeen); Referentiekader; Taalpsychologie; Langage; Cognition; Espace; Temps (Philosophie); Perception spatiale; Psycholinguistique; Electronic books; Electronic books